Scientific conference: Structural anthropology today. In honor of Claude Levi- Strauss, Faculty of Philosophy of Belgrade University, 28-29. November, 2008. - Dragana Antonijević (University of Belgrade, 2016)
On the occasion of the one hundredth birthday of the founder of structural anthropology,and one of the greatest anthropologists and intellectuals of the XX century, Claude Levi-Strauss, the Department of Ethnology and Anthropology of the Faculty of Philosophy of Belgrade University held a scientific conference with an aim to present and evaluate achievements, critical reviews and reception of structuralism in contemporary anthropology.